Pengaruh Penambahan Bioaktivator Em-4 (Effective microorganism) dan Mol (Mikroorganisme Lokal) Nasi Basi Terhadap Waktu Terjadinya Kompos - Ilham Ramaditya; Hardiono Hardiono; Zulfikar Ali As (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2017)
Abstract: Effect Of Addition Bio-Activator EM-4 (Effective microorganism) And Mol (Microorganism Local) Casserole Rice On Timing Of Compost. Composting is the decomposition of organic matter into simple materials is done naturally with the help of microorganisms , but the composting process that occurs naturally long and slow so indispensable ingredient bioactive able to accelerate the composting process. The help of a solution of EM - 4 (Effective microorganism) and MOL (Local Microorganisms) rice casserole that can be accelerated < 2 months . This study aims to determine differences in the addition of EM - 4 bio-activator (Effective Microrganism) with MOL (Micro Organism Local) Rice Casserole to the time of the compost. The method used in this study is experimental which has been experimenting with the observed variables such as time of compost from each - each treatment well control , EM - 4 as well as the addition of a solution MOL stale rice. Then after the data collected will be followed by a test using a One Way Analisys of Variance , the provisions of P value < alpha (0.05). The results showed that the value of p < alpha (0.05) . So there is the effect of the time difference with the help of compost activator EM-4/MOL rice. Then the three treatments of the fastest time of the end of the composting process is treatment with the addition of a solution of the stale rice MOL (15 days). Based on the results of the study can be recommended to accelerate the composting time can be used activator in the form of EM - 4 or with the help of a solution-based MOL stale rice. Keywords: Compost; EM – 4; MOL Rice Basi; Time Occurrence Compost.